2016
DOI: 10.3892/br.2016.777
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol and exercise

Abstract: Abstract. Although it is recommended for a healthy lifestyle, moderate exercise is known to lead to oxidative stress, inflammation and muscle injury. Hence there are efforts to develop dietary strategies to counter the oxidative stress caused by physical activity. Recently, there has been an interest in the capability of resveratrol (RES) to modulate physical performance and prevent oxidative stress. Despite the inconsistency among reports regarding the topic, it has been suggested that RES delays fatigue by h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 82 publications
0
53
0
8
Order By: Relevance
“…Hence, the intense effort to develop dietary strategies to counter the oxidative stress caused by physical activity (11). It has been known that Vitamin C has preventive role in tissue damage which is occurred by free radicals, thereafter it has been postulated that may prevents oxidative damage in sportsmen (12).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the intense effort to develop dietary strategies to counter the oxidative stress caused by physical activity (11). It has been known that Vitamin C has preventive role in tissue damage which is occurred by free radicals, thereafter it has been postulated that may prevents oxidative damage in sportsmen (12).…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation of polyphenols like resveratrol has previously been shown to minimize the deleterious effects of exercise-induced muscle damage and aid in recovery [21]. It is therefore likely that RES could also have therapeutic application in the context of inflammatory muscle injury and may be an ergogenic aid for clinically treating muscle injuries after a contusion injury.…”
Section: Ivyspringmentioning
confidence: 99%
“…In particular, a previous study reported low miR-9 expression in the knee tissues of patients with OA which may be related with the enhanced level of apoptosis in chondrocytes (27). In addition, miR-9 can negatively regulate the expression of NFkB1, thus suggesting that a reduction in miR-9 expression may increase the expression of NF-κB and therefore inhibit cell proliferation (29,(30)(31)(32) In conclusion, treatment with Res downregulates MALAT1 expression, and MALAT1 may function as a molecular sponge of miR-9. In addition, miR-9 can directly target NF-κB, and as an inflammatory cytokine NF-κB can induce apoptosis in chondrocytes contributing to the development of OA.…”
Section: Discussionmentioning
confidence: 99%